PENGARUH MOTIVASI DAN GAYA KEPEMIMPINAN TERHADAP KINERJA PEGAWAI PADA KANTOR DINAS PERINDUSTRIAN DAN PERDAGANGAN PROVINSI SULAWESI SELATAN - Idham Mulyadi; Muh Ikram Idrus; Muh Akib Agussalim (Jurnal Ilmu Manajemen Profitability, 2020)
This study aims to analyze the effect of motivation and leadership style to employee performance. This research was held at the Office of Industry and Trade of South Sulawesi Province. The sample of this study was 64 respondents.  This study is a quantitative research and analysis methods of data using multiple linear regression. The results of this study indicate that the variables of motivations and leadership style to employee performance. In partial leadership style does not significantly affect the performance of employees while variable motivation significantly affect the performance of employees at a significance level of less than 0,05 or 5%.